Scutellaria baicalensis, the golden herb from the garden of Chinese medicinal plants - Zhao, Qing; Chen, Xiao-Ya; Martin, Cathie (Science bulletin (Beijing), 2016)
Scutellaria baicalensis Georgi, or Chinese skullcap, has been widely used as a medicinal plant in China for thousands of years, where the preparation from its roots is called Huang-Qin. It has been applied in the treatment of diarrhea, dysentery, hypertension, hemorrhaging, insomnia, inflammation and respiratory infections. Flavones such as baicalin, wogonoside and their aglycones baicalein wogonin are the major bioactive compounds extracted from the root of S. baicalensis. These flavones have been reported to have various pharmacological functions, including anti-cancer, hepatoprotection, antibacterial and antiviral, antioxidant, anticonvulsant and neuroprotective effects. In this review, we focus on clinical applications and the pharmacological properties of the medicinal plant and the flavones extracted from it. We also describe biotechnological and metabolic methods that have been used to elucidate the biosynthetic pathways of the bioactive compounds in Scutellaria.